PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PEGAWAI MADRASAH ALIYAH ASWAJ AMBUNTEN - Mohammad Rofik (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
This research was conducted to find out why employees perform Turnover Intention. This study was conducted on employees who work at Madrasah Aliyah Aswaj Ambunten Timur. Turnover Intention is defined as the intensity of employees who want to resign from a company or institution where they work. There are two independent variables in this study, namely work conflict and work stress. The data collection technique used a questionnaire with several indicators of independent and dependent variables. The sample in this study used a saturated sample where the total population was the same as the number of samples, namely 47 employees.